Metabolite gradients and carbohydrate translocation in rosette leaves of CAM and C3 bromeliads - Popp, Marianne (The New phytologist, 2003)
•   The Bromeliaceae encompass predominantly rosette, terrestrial or epiphytic species, including C3 and crassulacean acid metabolism (CAM) photosynthetic types within its three subfamilies. Here, leaf diurnal changes and longitudinal gradients of soluble sugars, organic acids and starch, were quantified to estimate the rates of carbohydrate translocation from mature leaves of C3 and CAM species. •   Leaves of Ananas comosus, Aechmea fendleri, Bromelia humilis, Guzmania mucronata, Tillandsia fendleri, Tillandsia flexuosa and Tillandsia utriculata, were sampled at the base, middle, and upper sections during the day. We measured osmolality in sap from frozen subsamples, sugars and organic acids in hot-water extracts from microwave-dried subsamples, and starch hydrolysed with α-amylase or 1.1% HCl. •   CAM activity was expressed by malate accumulation, citrate was present, but fluctuations were not significant. Nocturnal reductions in sucrose in bromelioid CAM species accounted for most of the acidification requirements. Tillandsioid CAM species used starch for acid synthesis. Both CAM and C3 bromeliads exported significant amounts of hexose during the night, particularly from the leaf base. •   Leaf bases of CAM species showed lowest acid accumulation but similar or more positive δ13 C-values to the active CAM sections. Exported carbohydrates probably derive from carbon fixed during the night period